1998
DOI: 10.1099/00222615-47-9-767
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of enhanced toxin production by Clostridium difficile in biotin-limited conditions

Abstract: Production of toxins A and B by Clostridium difficile is enhanced in a defined medium with biotin-limited conditions. In the present study compounds inhibitory to enhanced toxin production by a C. dij$jjcile strain were examined. Increases in biotin concentration from 0.05 nM to 50 nM accelerated growth and inhibited enhanced toxin production. Asparagine, glutamic acid and glutamine (10 mM) showed an effect on growth and toxin production similar to that of biotin. Lysine (10 mM) suppressed growth and inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
(13 reference statements)
2
22
2
Order By: Relevance
“…Toxin mRNA levels have been shown to respond to a variety of environmental signals such as temperature, nutrient concentrations and antibiotics (Karlsson et al, 1999(Karlsson et al, , 2003Yamakawa et al, 1998;Nakamura et al, 1982). We checked for the downregulation of toxin mRNAs by nutrient depletion or other signalling molecules using real-time PCR.…”
Section: Co-culture Causes Complete and Persistent Loss Of Toxicitymentioning
confidence: 99%
“…Toxin mRNA levels have been shown to respond to a variety of environmental signals such as temperature, nutrient concentrations and antibiotics (Karlsson et al, 1999(Karlsson et al, , 2003Yamakawa et al, 1998;Nakamura et al, 1982). We checked for the downregulation of toxin mRNAs by nutrient depletion or other signalling molecules using real-time PCR.…”
Section: Co-culture Causes Complete and Persistent Loss Of Toxicitymentioning
confidence: 99%
“…Toxin synthesis is normally upregulated during entry into the stationary growth phase in tryptone/peptone-yeast media (Dupuy & Sonenshein, 1998;Karlsson et al, 1999), and is associated with the induction of many other C. difficile proteins that are repressed together with the toxins by the presence of glucose, cysteine and proline (Karlsson et al, 2000). In addition, arginine, glutamine, biotin and carbonate influence toxin production, further supporting a link between carbon/amino acid metabolism and toxin production (Ikeda et al, 1998;Karasawa et al, 1997;Karlsson et al, 1999;Maegawa et al, 2002;Yamakawa et al, 1996Yamakawa et al, , 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Toxin expression may differ 100,000-fold between toxin-positive isolates of C. difficile in vitro (14) but the underlying reason is not understood. Previous studies have shown that regulation of toxin production in C. difficile may be affected by amino acid levels, as demonstrated in defined media during biotin starvation (25) and in complex media (12,18). High toxin levels are observed in complex media deprived of glucose (4,12).…”
mentioning
confidence: 99%
“…The onset of C. difficile growth in the large intestine, followed by C. difficile-associated diarrhea (CDAD), is thought to be caused by the reduction of protective colonic microbiota, especially by antibiotic treatment (14). Toxin production by C. difficile has been demonstrated to be dependent on the nutrient level of the growth medium (7,10,12,18,24,25). The type and amount of nutrients present have been shown to affect growth of C. difficile in a continuous culture system containing a complex microflora (23,26), suggesting that competition for nutrients in the colon plays a role in colonization by the pathogen and in the development of CDAD.…”
mentioning
confidence: 99%